Repurchase Model Through Purchase Decision: Analysis of Product and Price Effect on Dulux Paint Consumers in DKI Jakarta and Tangerang Area - Nico Gerard Doan, Ali; Ali, Hapzi (Dinasti Publisher, 2021)
The purpose of this study was to determine how to analyze and how much, the following influence on the significance of product quality and price on purchasing decisions that have implications for repurchasing. This research is a census, the number of objects in the population with 100 respondents. The objective to be approved in this study is to prove empirical evidence regarding variable product quality and price, on purchasing decisions in choosing wall paint products, through purchasing decisions this research will also analyze the effect product quality and price against repurchase. The results show that the variable conditions of product quality and price have an impact on purchasing decisions in the good category, as well as the effect of product quality and price on repurchases, with positive and significant results, namely in the situation, if the product quality and price are increased then, will have an impact on increasing purchase and repurchase decisions